Quality of life in patients with recurrent ovarian cancer treated with niraparib versus placebo (ENGOT-OV16/NOVA): results from a double-blind, phase 3, randomised controlled trial. Issue 8 (August 2018) - Oza, Amit M; Matulonis, Ursula A; Malander, Susanne; Hudgens, Stacie; Sehouli, Jalid; del Campo, Josep M; Berton-Rigaud, Dominique; Banerjee, Susana; Scambia, Giovanni; Berek, Jonathan S; Lund, Bente; Tinker, Anna V; et al.
Summary: Background: Quality of life (QOL) has become an important complementary endpoint in cancer clinical studies alongside more traditional assessments (eg, tumour response, progression-free survival, overall survival). Niraparib maintenance treatment has been shown to significantly improve progression-free survival in patients with recurrent ovarian cancer. We aimed to assess whether the benefits of extending progression-free survival are offset by treatment-associated toxic effects that affect QOL. Methods: The ENGOT-OV16/NOVA trial was a multicentre, double-blind, phase 3, randomised controlled trial done in 107 study sites in the USA, Canada, Europe, and Israel. Patients with recurrent ovarian cancer who were in response to their last platinum-based chemotherapy were randomly assigned (2:1) to receive either niraparib (300 mg once daily) as a maintenance treatment or placebo. Randomisation was stratified based on time to progression after the penultimate platinum-based regimen, previous use of bevacizumab, and best response (complete or partial) to the last platinum-based regimen with permuted-block randomisation (six in each block) using an interactive web response system. The trial enrolled two independent cohorts on the basis of germline BRCA (g BRCA ) mutation status (determined by BRAC Analysis Testing, Myriad Genetics, Salt Lake City, UT, USA). The primary endpoint of the trial was progression-free survival, and has already been reported. In this study, we assessed patient-reported outcomes (PROs) in the intention-to-treat population using the Functional Assessment of Cancer Therapy–Ovarian Symptoms Index (FOSI) and European QOL five-dimension five-level questionnaire (EQ-5D-5L). We collected PROs from trial entry every 8 weeks for the first 14 cycles and every 12 weeks thereafter. If a patient discontinued, we collected PROs at discontinuation and during a postprogression visit 8 weeks (plus or minus 2 weeks) later. We assessed the effect of haematological toxic effects on QOL with disutility analyses of the most common grade 3–4 adverse events (thrombocytopenia, anaemia, and neutropenia) using a mixed model with histology, region, previous treatment, age, planned treatment, and baseline score as covariates. This study is registered withClinicalTrials.gov, numberNCT01847274 . Findings: Between Aug 28, 2013, and June 1, 2015, 553 patients were enrolled and randomly assigned to receive niraparib (n=138 in the g BRCA mut cohort, n=234 in the non-g BRCA mut cohort) or placebo (n=65 in the g BRCA mut cohort, n=116 in the non-g BRCA mut cohort). The mean FOSI score at baseline was similar between the two groups (range between 25·0–25·6 in the two groups). Overall QOL scores remained stable during the treatment and preprogression period in the niraparib group; no significant differences were observed between the niraparib and placebo group, and preprogression EQ-5D-5L scores were similar between the two groups in both cohorts (0·838 [0·0097] in the niraparib group vs 0·834 [0·0173] in the placebo group in the g BRCA mut cohort; and 0·833 [0·0077] in the niraparib group vs 0·815 [0·0122] in the placebo group in the non-g BRCA mut cohort). The most common adverse events reported at screening (baseline) were lack of energy (425 [79%]; 97 [18%] reporting severe lack of energy), pain (236 [44%]), and nausea (118 [22%]). All symptoms, except nausea, either remained stable or improved over time in the niraparib group. The most common grade 3 or 4 toxicities observed in the niraparib group were haematological in nature: thrombocytopenia (124 [34%] of 367 patients), anaemia (93 [25%]), and neutropenia (72 [20%]); disutility analyses showed no significant QOL impairment associated with these toxic effects. Interpretation: These PRO data suggest that women who receive niraparib as maintenance treatment for recurrent ovarian cancer after responding to platinum treatment are able to maintain QOL during their treatment when compared with placebo. Funding: TESARO.